2004
DOI: 10.1055/s-2004-832627
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Chemical and Functional Analysis of Catuaba Preparations

Abstract: Fourteen commercial samples of the popular Brazilian aphrodisiac Catuaba specified as bark drugs of Anemopaegma, Erythroxylum and Trichilia species were examined for identity and purity. Only a minority of the examined Catuaba samples contained the crude drugs claimed on the labels. More than half of the products were adulterated with different crude drugs. The majority of the samples contained a bark originating from Trichilia catigua. The TLC fingerprints confirmed the heterogeneity, in 50% of the samples tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
3
8
0
5
Order By: Relevance
“…Marques 2 described the differences among the species known as "catuaba" and determined that T. catigua is the main species that is sold as "catuaba" in Brazil. The same conclusion was reached by Kletter et al 3 and Daolio et al 4 The bark of T. catigua has been traditionally used as a health and mental tonic, and especially as a sexual stimulant. 3,5 Some pharmacological studies of this bark have reported antimicrobial, trypanocidal, antinociceptive, vasorelaxant or dopamine-mediated antidepressantlike effects.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Marques 2 described the differences among the species known as "catuaba" and determined that T. catigua is the main species that is sold as "catuaba" in Brazil. The same conclusion was reached by Kletter et al 3 and Daolio et al 4 The bark of T. catigua has been traditionally used as a health and mental tonic, and especially as a sexual stimulant. 3,5 Some pharmacological studies of this bark have reported antimicrobial, trypanocidal, antinociceptive, vasorelaxant or dopamine-mediated antidepressantlike effects.…”
Section: Introductionsupporting
confidence: 63%
“…The same conclusion was reached by Kletter et al 3 and Daolio et al 4 The bark of T. catigua has been traditionally used as a health and mental tonic, and especially as a sexual stimulant. 3,5 Some pharmacological studies of this bark have reported antimicrobial, trypanocidal, antinociceptive, vasorelaxant or dopamine-mediated antidepressantlike effects. [5][6][7][8][9][10] The bark contains a high concentration of polyphenols (6.96 ± 0.11%; RSD 1.57%) including flavan-3-ols and phenylpropanoid derivatives, 5,11 as well as tropane alkaloids.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…A confusão na identificação iniciou-se no início do século 20 com uma tese de doutorado e perdura até os dias atuais (DAOLIO et al, 2008;KLETTER et al, 2004;TABANCA et al, 2007). DAOLIO et al, 2008;KLETTER et al, 2004).…”
Section: Células Epidérmicas Do Tegumento Em Vista Frontal (Escala: 2unclassified
“…As análises, em conjunto, permitiram verificar que os quatro lotes de catuaba se tratavam da espécie T. catigua, fato que também foi anteriormente observado na literatura (BELTRAME et al, 2006;DAOLIO et al, 2008), apesar da 1ª edição da Farmacopéia (1929), revogada, oficializar órgãos subterrâneos de A. mirandum. Kletter et al (2004) realizaram um projeto de avaliação da qualidade de amostras comerciais de catuaba, onde foi possível confirmar a prevalência das cascas de caule de T. catigua dentre as DVs presentes no mercado. Entretanto, os cuidados com a qualidade do material estudado se mostrou precária, com contaminação e problemas nos rótulos e armazenamento, da mesma forma que demonstram os resultados presentes nesta dissertação.…”
Section: Perfil Cromatográficounclassified